KEDUDUKAN BANK INDONESIA SEBAGAI PEMOHON PAILIT BANK SETELAH BERDIRINYA OTORITAS JASA KEUANGAN - RIKKI JOSUA SILITONGA (PREMISE LAW JURNAL, 2016)
In Law No. 9/2016 on Prevention and Handling Financial System Crisis of Systemic Effect, it is stated that filing for bankruptcy cannot be made by a non-performing Bank because it will affect national economic system, but it can be made by a non-performing Bank which does not have any systemic effect on national economic system. This is one of the indicators of a Bank which can file for bankruptcy in Indonesia. Based on the analysis on the role of Bank of Indonesia when legal standing of filing for bankruptcy by a certain Bank is shifted to the Financial Service Authority, it is necessary to consider the status of the Bank, whether it has systemic effect when it files for bankruptcy or not. The Financial Service Authority can be asked to consider or coordinate with Bank of Indonesia in determining systemic effect of a certain Bank as far as Bank of Indonesia still has its authority in macro-prudentials. Keyword: Bankrupcy, Bank of Indonesia, Financial Service Authority